Processed Multibeam Sonar Data (version 2) from the Amundsen Sea acquired during Nathaniel B. Palmer expedition NBP1005 (2010) ... - Yager, Patricia (Interdisciplinary Earth Data Alliance (IEDA), 2013)
This data set was acquired with a Kongsberg model EM120 multibeam sonar system during Nathaniel B. Palmer expedition NBP1005 conducted in 2010 (Chief Scientist: Dr. Patricia Yager). These data files include Sidescan, Acoustic Backscatter, Swath Bathymetry data and were processed at sea using the open source MB-System multibeam sonar processing software. Data were acquired as part of the project(s): ASPIRE (Amundsen Sea Polynya International Research Expedition), and funding was provided by the U.S. National Science Foundation. ...